Return migration and entrepreneurship in Cameroon - Sévérin Tamwo; Ghislain Stéphane Gandjon Fankem; Dieudonné Taka (The United Nations University World Institute for Development Economics Research (UNU-WIDER), 2022)
In this paper, we examine the determinants of the entrepreneurial behaviour of returnees to Cameroon based on original survey data from 2012. Contrary to the existing literature, we focus on the skills received from abroad without omitting the effect of savings. We distinguish between three types of competences related to qualifications. We also differentiate between the probability of starting a business in the primary sector and the probability of starting a business in the tertiary sector. The main results, obtained from a probit model, show that: (i) degrees and qualifications and qualifications acquired abroad do not positively influence the probability of migrants to undertake a new activity once back home; in contrast, accumulated savings, captured by the time spent abroad, have a positive influence; (ii) other qualifications have no influence on the entrepreneurial behaviour of return migrants; and (iii) the entrepreneurial behaviour of return migrants is not oriented towards the primary sector but rather towards the tertiary sector. These results are robust when we account for endogeneity
Keywords: C25; F22; J61; L26; 330; returnees; skills; entrepreneurship; probit model; endogeneity; Cameroon